An Analysis of Tourists’ Use and Assessment of Tourist Infrastructure in the Ivano-Frankivsk and Transcarpathian Regions of Ukraine - Olena Pobihun; Liudmyla Arkhypova; Yaroslava Korobeinykova; Sofiia Kachala; Victoria Hryniuk (Studia Regionalne i Lokalne)
The main tasks of the study were to analyse and assess the state of infrastructure near tourist facilities based on the results of a survey, as well as identify problems and prospects of infrastructure development. Information was collected regarding the time spent in the settlements of the Ivano-Frankivsk and Transcarpathian regions when visiting tourist facilities, how to get there, which food and accommodation establishments to choose, how much one is willing to spend, additional services, leisure facilities, etc. Most of the tourists rated the recreational infrastructure as “excellent” and “good”. The respondents expressed several wishes: the improvement of the infrastructure, the beautification of the territory, information support, increase in the number and quality of public restrooms, and the revitalisation of cultural and entertainment events.